Dosis de carbón vegetal en la dieta alimenticia y rendimiento productivo de aves criollas mejoradas en Zungarococha, Loreto, 2024 - Sanchez Quichua, Luz Dina (2025)
The objective of the research was to evaluate the effect of different doses of charcoal on the productive performance of improved landracebirds. The methodology was experimental, using a completely randomized design with 5 treatments that varied in the proportion of charcoal included in the diet. The population studied consisted of 300 birds, of which 125 were selected for the experiment and distributed equally among the treatments. The data collected included initial and final weight, weight gain, feed conversion and feed efficiency. The results showed that the inclusion of charcoal in the diet significantly improved productive performance, particularly at higher doses (4%), increasing weight gain and feed efficiency. Feed conversion was optimized with higher percentages of charcoal, which indicated better feed use. The conclusions highlighted that charcoal has a positive impact on poultry productivity, with no adverse effects. It is proposed that this additive is a viable alternative to improve poultry performance. The research recommendations suggest continuing to explore the benefits of including charcoal at different stages of growth and in other bird species, as well as conducting long-term studies to assess the sustainability and economic implications of using charcoal in poultry feed.